The welfare costs of traffic congestion in São Paulo Metropolitan Area - Vale, Ricardo Campante Cardoso (2018)
This thesis presents new evidences of negative impacts of traffic congestion in São Paulo Metropolitan Area, indicating that the omission or retardation of policy to alleviate that charges society with a high cost. Besides that, we shed light on Waze application\'s impacts, evidencing GPS-based participatory navigation is a key element of the traffic in the contemporary cities. Induced by the economic theory, one can see that traffic slowness derived from the general demand for automotive vehicles corresponds to a social cost. With the objective of translating this cost to monetary units, we developed an approach that matches the 2012 Origin-Destination survey to Google Maps data. An econometric travel mode choice model is estimated and through that we infer the Value of Time for trips. From counterfactual analysis for travel duration, we estimate the delays of the trips in relation to a hypothetic free flow situation. Joining the calculations, we estimate that 89% of the trips motivated by work in São Paulo are retarded by traffic frictions, generating an annual welfare cost that amounts to R$7.338 billions. Additionally, we analyze widespread Waze malfunctioning at 10/23/2017. Combining congestion data to the Value of Time, we estimate that the Waze bug approximatedely tripled the welfare costs in regards to a typical day, showing the magnitude of mass effects that a social navigation application is able to trigger.